CAPIM-LIMÃO - Cymbopogon citratus (D.C.) STAPF: SUBSIDY TO IMPROVMENT OF QUALITY IN THE CROP, INDUSTRIALIZATION AND MARKETING IN PARANÁ STATE - Gomes, Eliane C.; Negrelle, Raquel R. B. (Scientia Agraria, 2006)
Regarding the promising market of natural products and its crescent requires, associated with a lack of knowledge in various areas, particularing studies that relates the quality and segments of produtctive chain of all sorts of species, the objetive of this work was to realize studies about the quality of Cymbopogon citratus (D.C.) Stapf in the crop, industrialization and marketing, to link with its possible causes and to propose solutions to envolved agents in the productive chain of species, in Paraná State, aiming at to subsidy the improvement of the system in general. This work involved field research, interviews with producers and agents of productive chain, besides diferent laboratories analysis of quality of crude product, processed or final available to consumer market in Curitiba (2000- 2003). The results of this research compose the nine chapters that integrate the thesis. The chapters 1 and 2, introduce extensive revision of botanical, ecological, phytochemical and pharmacological aspects of lemon grass, were identified the main chemical compound as the aldehyde citral, and the main pharmacological actions were: analgesic, anti-microbial, insecticide and anti-tumor. The chapter 3, results of the research to give subsidies for the comprehension of chain production of lemon grass in Paraná State. Identifyied as main components of the productive chain: the productive unit, the agroindustry, the industry (chemical, nutritive and pharmaceutical), the market (wholesale and retail) and the consumer ( interior and exterior). The chapter 4, a detailed view of proceedings associated to the crop in this State, evidencing the congruency and divergency of field research data and what is reported on literature as been suitable for this crop. The chapter 5 refers the harvest and postharvest (processing, package and storage) of lemon grass executed by producers of Paraná State, to give subsidies to the offer of good quality product. The chapter 6 introduces informations about packaging and labelling of lemon grass tea trademarks commercialized by supermarkets in Curitiba city, were evidenced nineteen trademark. The chapter 7 presents data from an explorative-descriptive research that took place in the supermarkets sector to evaluate the quality and adequability of packaging and storage areas of teas considering current legislation. Besides providing a general view about the situation of tea storage, this research had the purpose of creating a base instrument to develop the sanitary inspection in this sector of marketing. The research presented in chapter 8 aimmed to evaluate four lemon grass tea trademarks marketed in the metropolitan area of Curitiba, regarding their microbiology and physical-chemical quality based on the Brazilian Health Departament food legislation. Evidenced bacterial contamination with Escherichia coli and others, besides moulds and yeasts, with presence of Aspergillus niger in two samples. Salmonellasp and aflatoxins were absent. The chapter 9 synthetizing the diferent problems and strangulations evidenced in the previously cited chapters, is presented a group of proposes and recommendations to the economic agents that act and carry in productive chain of lemon grass in Paraná State.